Disbudporapar Communication Strategy in Increasing Tourist Visits Nature in Karo District - Noviyanti Br Sembiring; Humaizi; Lusiana Andriani Lubis (Indonesian Journal of Advanced Research, 2024)
This research aims to analyze how the Karo Regency DISBUDPORAPAR communication strategy increases tourist visits and to analyze whether there are obstacles in implementing the Karo Regency DISBUDPORAPAR communication strategy. This researcher uses AIDDA Theory or often also called AA Procedure (from attention to action procedure), a theory put forward by Wilbur Schraman. AIDDA theory stands for Attention (attention), Interest (interest), Desire (desire), Decision (decision), Action (action/activity). Where this research uses a qualitative approach to data collection through interviews, observation, and photo documentation, and ends with data analysis. This is to describe the data findings and analysis of the data used. The results found in this research are that DISBUDPORAPAR has implemented the provisions contained in the AIDDA theory by implementing communication strategies to increase natural tourism visits in Karo Regency. Researchers also found that DISBUDPORAPAR carried out marketing communication strategies via Instagram, Tiktok, YouTube, Facebook, and the Karo Highland Tourism application. The obstacles in implementing communication strategies are due to budget limitations, thereby narrowing the space for DISBUDPORAPAR socialization activities.